A Model of the Confidence Channel of Fiscal Policy. Issue 7 (15th September 2016) - GUIMARAES, BERNARDO; MACHADO, CAIO; RIBEIRO, MARCEL
Abstract : This article presents a simple macroeconomic model where government spending affects aggregate demand directly and indirectly, through an expectational channel. Prices are fully flexible and the model is static, so intertemporal issues play no role. There are three important elements in the model: (i) fixed adjustment costs for investment, which create an inaction zone; (ii) noisy idiosyncratic information about the aggregate economy; and (iii) imperfect substitution among private goods and goods provided by the government. An increase in government spending raises demand for private goods and may prevent a coordination failure. The optimal level of government expenditure is high when the desired level of investment is low, which we interpret as a time of low economic activity.